Media education role in achieving physical education goals in Poland - Lubońska, Magdalena (Kultura-Społeczeństwo-Edukacja, 2021)
Indirect education found and is still finding its source in various media for a long time. Technological advancement results in the educators having an increased ability to use new tools in education. The goal remains the same but the social conditions impose a new identity – the subject teacher evolves into a media one. In the school system, necessary corrections have been introduced to the most important documents and the curricula, but there is still a lack of knowledge on what media education looks like in practice in specific national realities. The review article shows how goals determined by the curricula are already realized through new media in Poland and for which goals the didactic activities should be expanded. In the thematic block concerning physical activity, there is an entry: “The contents of this area have been enriched with modern forms of movement, physical activities from other European countries and use of modern technologies to monitor and plan physical activity” (MEN, 2017: 191). When organizing activities in the classroom area and with the right equipment, conducting lessons with the use of the media is not a problematic task. But are the PE teachers in a similarly comfortable position? It turns out that the development of information technology is conducive to the achievement of the objectives of this subject as well. The literature review and the solutions used so far in the school system are the basis for the thesis of a correlation between the ways in which modern media are used and the formation of the students’ attitudes towards physical culture.